GENOMIC ANALYSIS AND EXPRESSION INVESTIGATION OF STEROLEOSIN GENE FAMILY IN ARABIDOPSIS THALIANA - U. Aziz; N. Saleem; T. Tang; M. Zhang (Journal of Animal and Plant Sciences, 2020)
Despite having growing evidence discussing the role of steroleosins in crop plants, their systemic analysis has not been worked extensively. Therefore, bioinformatics tools were employed to study Arabidopsis (Arabidopsis thaliana)steroleosin in comparison with reported Brassica napus and pine steroleosins.  Based on molecular weight, eight steroleosins in Arabidopsis were divided into two groups, L-steroleosin (alkalescence) and H-steroleosin (acidity except At5g50770). Phylogeny analysis suggested that H-steroleosins in Arabidopsis are primitive. Moreover, phylogeny, protein alignment, motif analysis and gene structure analysis revealed that the reported steroleosins in B. napus are closely related to H-steroleosins. Similarly, Gene structure analysis revealed an insertion of 10 residues at the C-terminal of H-steroleosin which makes it relatively larger as compared to L-steroleosins. According to the Protein-protein interactions, Arabidopsis steroleosins are interrelated with genes involved in fatty acid biosynthesis and stress tolerance. Duplication studies suggest that among the steroleosin genes in Arabidopsis, segmental duplications are newly developed. Expression analysis suggests that H-steroleosins mainly express in seed tissue, while L-steroleosins diverge in two directions: expression or repression in all tissues. The upstream sequence analysis suggests that Arabidopsissteroleosinsare involved in lipid metabolism and the brassinosteroid signaling pathways. The roles of steroleosins for stress responses are indicated by their induced expression under stress and abscisic acid treatments. Therefore, further investigations are required to evaluate the functions of steroleosins in plants.
Keywords: Steroleosins classification; Expression analysis; Potential functions; Evolution; Arabidopsis